Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Fitur Go-Food PT Gojek Indonesia - Kuncoro, Danang Dwi; Lestari, Wuryaningsih Dwi (Jurnal Prodi Fakultas Ekonomi-UISU, 2023)
Along with the rapid development of the times and advances in education, a more prosperous economy, socio-cultural changes in society, and the development of sophisticated science and technology, can facilitate human activities. This is in line with the term industrial revolution 4.0 where one of its characteristics is technological advancement and the era of digitalization. The purpose of this study was to analyze the effect of service quality and price on customer satisfaction for the go-food feature of pt.gojek indonesia. This research method is quantitative, the population of this research is all students of Universitas Muhammadiyah Surakarta. And the number of samples of this study were 200 respondents. The results of the study are service quality has a positive and significant effect on customer satisfaction. Price has a positive and significant effect on customer satisfaction.